Formulation and Evaluation of Gelatin Nanoparticle Moisturizing Gel from Mesocarp Extract of Watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] as an Antioxidant - Sari Okzelia; Semitha Azzahara; Kosasih Kosasih; Silfera Yanti (Journal of Sciences, Islamic Republic of Iran)
Human skin might get attacked by free radicals therefore, antioxidants are needed. Mesocarp of watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] has natural antioxidant compounds such as citrulline. Antioxidant compounds were formulated into gel preparation with nanoparticle technology that aimed to facilitate the absorption of an active substance. The purpose of this study was to formulate an antioxidant moisturizing gel that contained gelatin nanoparticles of mesocarp extract of watermelon (GNMW). The stages of research included the extraction, production, and characterization of nanoparticles, formulation of gel preparations with various concentrations of 0.0114% (F1), 0.0228% (F2), and 0.0342% (F3), evaluation of gel preparations, observation of antioxidant activity using DPPH method and skin moisture test. The nanoparticles produced had an irregular shape, size of 200.3 nm, polydispersity index of 0.288, and zeta potential value of +16.11 mV. The nanoparticle gel had a slightly viscous texture, clear color, and homogeneous, with a pH value of 6.61 – 7.22; viscosity of 14740 – 17180 cP; spread-ability of 5.3-6.5 cm; and did not irritate the skin. The results of the antioxidant activity of the extract and nanoparticles were 110.90 μg/mL and 114.16 μg/mL, respectively. Nanoparticle gel of F1, F2, and F3 had IC50 values of 149.52 μg/mL; 138.44 μg/mL; and 127.10 μg/mL, respectively. The gels could increase skin moisture content in the range of 38.81% - 63.19%. Mesocarp extract of watermelon which was made into nanoparticles with gelatin carrier could be formulated into a moisturizing gel, met good gel parameter standards, and had moderate antioxidant activity.